Etty Hillesum: a força da vida e o mistério de Deus - Teixeira, Faustino (Revista Eclesiástica Brasileira, 2019)
A presença da jovem mística, Etty Hillesum (1914-1943), mudou o panorama da visão tradicional da mística, apontando um caminho singular de alguém que vem de um mundo secular, com traços de liberdade e busca de autenticidade. Alguém que se aproximou de forma singular do mistério maior, sem nome, enfrentando com altivez condições adversas de um campo de concentração e cavar no fundo de si a presença acolhedora de Deus. É uma mística inspiradora, que consegue desentranhar nas condições mais adversas a consciência da beleza da vida e um sentido mais profundo para continuar acreditando num mundo melhor. O artigo visa apresentar a reflexão mística de Etty, a partir dos passos indicados em seu diário e suas cartas, bem como de estudos de especialistas sobre seu itinerário espiritual. Abstract: The presence of the very young woman and mystic Etty Hillesum (1914-1943) changed the overall picture of the traditional aproach of mysticism, which points out the sole path of someone who comes from a secular world, showing traces of freedom and a deep search for authenticity. Someone who was able to approach in a unique way the greatest, unnamed mistery, facing hostile conditions in a concentration camp and digging in her own depths the welcoming presence of God. She is an inspiring mystic that can reveal even in the most adverse conditions the awareness of life’s beauty and also a deeper meaning to continue believing in a better world. The article aims to present Etty’s mystical reflection, from the writings of her journal and letters and also from the analysis of scholars about her spiritual journey. Keywords: Mysticism; Interior life; God; Openness; Hospitality.